Українські обрії Північного Причорномор’я (історико-археологічні спостереження) - Біляєва, С.О. (Археологія і давня історія України, 2021)
У статті приділено увагу основним етапам та
особливостям формування та розвитку українського історико-культурного процесу на теренах Північного Причорномор’я, ключовим факторам, які мали вплив на його особливості на основі історико-археологічного вивчення регіону. Розглянуті актуальні питання заселення, та етнокультурного обличчя регіону, відзначені перспективні напрямки подальших досліджень. The important role in the history of Ukrainian lands
belong to the North Pontic Area. Last decades the revision
of old position from one side and the growing of
the attention towards the problems of this region take
place. The beginning of own ethnical development of
Slavs tribes, known by «Ants» name or «Okrainni» by
Indo-Iranian language. On the next stage of history, the
tribes of Russ chronicle: Ulichi and Tyvertsy settled on
Black Sea region. Colonization of this area by the Slavs
lasted through more than 500 years, which created the
fundamental ethnical base of autochthone population.
With formation of Kyiv Russ the North Black Sea area
take the important place in political, economic, ethno
cultural and trade fields of the new country. The numerous
settlements fixed on the Lower Dnieper and
other rivers in spite of numerous nomadic tribes: every
society occupy the own part of the landscape in connection
from their economic type. In the of Post Kyiv Russ
and Lithuanian-Russ federation, the South Russ principalities
preserved their traditions and continue the
progressive development. At the end of the XIV — at
the beginning of XV centuries the new fortification line
built under the chief of the Great Prince Vitovt in the
North Black Sea Area, which opened the new stage of
fortification: stone fortresses. The brilliant example of
this kind is the first stone fortress Tyagin of the South
part of the Lithuanian-Russ principality, as a part of
the early Ukraine. In the time of Crimean-Ottoman
administration in region, the Christiania autochthone
population with Ukrainian part also, continue to live
in the North Black sea area and became the region of
Cossack colonization. The artefacts of Ukrainian culture
founded in the course of the archaeological excavation
(Akkerman, Ochakiv) even in the Ottoman fortresses.
The anthropological investigations support the
existence of great part of the settled population, which
take the considerable morphological contacts with
Ukrainians of the South, Central and West regions of
the XVII—XIX centuries. The important factor of the
living of Christian population, including Ukrainians,
was the existence and activity of the Brailiv metropolis
of the Konstantinopol patriarchate in the middle of
the XVI—XIX cent., which escape the large area from
Braila to Tyagin. The archaeological investigation of
the South Ukraine increase the possibility of the knowledge
of the Ukrainian history from the new modern
position.